A new subspecies of Iberis saxatilis (Brassicaceae) from Turkey - Oskay, Dilek (Phytotaxa, 2017)
Iberis saxatilis subsp. magnesiana Oskay subsp. nov. is identified as a new subspecies from Kocasivri Mt. (Manisa), west Anatolia, Turkey. Iberis saxatilis subsp. magnesiana is a local endemic, most similar to Iberis saxatilis L. subsp. saxatilis. Diagnostic characters of these related taxa are discussed. Habitat characteristics, distribution and conservation status of the new subspecies are also presented.